Kajian Modalitas Linguistik Fungsional Sistemik Pada Teks Debat Capres-Cawapres Pada Pilpres 2014-2019 Dan Relevansinya Dengan Pembelajaran Wacana Di Sekolah - Adul Aziz Faradi (RETORIKA: Jurnal Ilmu Bahasa, 2015)
This study research is the text about  debate candidate of President and Vice President election of the Republic of Indonesia in the year of 2014-2019  by using the theory of Systemic Functional Linguistics (LFS) which relevanced with text learning at school. This study deals with three functions of  languages. The are:   exposure, exchange and coupling experience, but on the vice presidential candidate debate is focused on the function of which is realized in the exchange rate system and the modalities of the value message in the context of ideology, culture, and situations that are at a frequency that dominates the text candidate debates in the year of 2014-2019 presidential and vice presidential election, and then a message describing the values behind the dominant frequency in the modalities that were realized in the context of ideology, cultural context and the context of the situation. Data was collected by the methods of formal and informal, with a note technique, consider doing the stage read the text carefully, analyzing the data in the form of the clause, and the classification of the data and the verification and validation of the data carefully and throughly, concluding the results of the research. Results of this study can be relevanced through discourse in school-related learning content and technical aspects and how to analyze the discourse of the text with LFS. Based on the analysis of text, fifth presidential and vice presidential debate in the Republic of Indonesia.  Presidential Election in the year of  2014-2019, found that in the text there are 1,150 clause consisting of 563 clauses for couples PS- HR and 587 clauses for couples JW -JK. From the number of the clauses contained modalities of 562 words with the details of the realization of modalities types of modulation (modulation) of 428 or 76.16%, while the type modalization  of 134 or 23.84%.  The result of the research on the text of the first debate using the whistleblower or the realization of modalities that the lowest at 77 or 13.71%. The second debate text using the revealer of modalities as much as 103 or 18.33%. The third debate text using the revealer of the most dominant modality that is equal to 149 or 26.51%. The fourth debate whistleblower text using modalities were 106 or 18.86% and the text of the fifth debate using whistleblower modality by 127 or 22.59%. The use of the realization of the most dominant modalities used in the fifth text of the debate is the realization of modalities categories * must, * Usuality * need, * should be included into the modalities of modulation types must * high, amounting to 218 or 38.79% compared with whistleblower or the realization of other modalities. Realization of modalities atleast  amount of occurrence is  more into the category of modality types modalities #medium frequency , # sometimes that includes modality type ^ low modalities frequency with each of 1 or 0.18%. From the analysis of the social context of language use in text-vice presidential candidate debate was found that both partners-vice presidential candidates both PS - HR and JW - JK uses modulation modality must be a* high level is the most dominant. This indicates that both partners-vice presidential candidates are using expressions filled with firmness values of leadership, high confidence value for the win, and religious values with intermediate modalities #Insya Allah and that aim to convince and attractive the sympathy of the audience in the presentation program -Program to be implemented. If they are elected. So, the message character values with high confidence and a spirit of optimism in reaching an expectation, the value of simplicity, democracy, courage and moral values have relevenasi about 85% with the discourse of learning in school tobe integrated based text or based on the  Curriculum of 2013.